Overview of skin cancer types and prevalence rates across continents - Roky, Amdad Hossain; Islam, Mohammed Murshedul; Ahasan, Abu Mohammed Fuad; Mostaq, Md Saqline; Mahmud, Md Zihad; Amin, Mohammad Nurul; Mahmud, Md Ashiq (Cancer pathogenesis and therapy, 2025)
Skin cancer is one of the most prevalent cancers in the world, and its incidence and mortality rates are increasing continuously, mostly in regions with white-skinned inhabitants. The types of skin cancer vary in their origin and clinical appearances and also differ in their extensiveness. The continents of the world have different scenarios of skin cancer prevalence. This review aims to explore the different types of skin cancer, their clinical features, and their worldwide prevalence based on the literature. Literature from different electronic databases, including Google Scholar, ResearchGate, PubMed, Scopus, Web of Science, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL), Elsevier, and Springer, were collected through a literature search using specific keywords such as “skin cancer”, “skin cancer types”, “melanoma”, “non-melanoma”, “skin cancer continental prevalence” or similar keywords. The search included English publications from 2000 to 2024. Melanoma skin cancer (MSC) ranks 17th in global prevalence, with the highest incidence and deaths occurring in Europe, However, Australia and New Zealand record the highest incidence and mortality rates. Asia has a lower incidence rate of melanoma, but a higher mortality rate. Superficial spreading melanoma (SSM) is the most common type of MSC. Non-melanoma skin cancers (NMSCs) have the highest incidence in North America, with the highest number of deaths occurring in Asia, Australia and New Zealand have the highest incidence rates for basal cell carcinoma (BCC). BCC is the most commonly diagnosed skin cancer worldwide and the most prevalent form of NMSCs; however, squamous cell carcinoma is the most aggressive form of NMSCs, causing more deaths. NMSCs are the most prevalent cancers worldwide, causing most skin cancer-related deaths. The prevalence of skin cancer rising globally, with several continents experiencing higher incidence and mortality rates. The types and subtypes of skin cancer are becoming more common among clinically diagnosed cancers. This review comprehensively describes skin cancer types and their prevalence worldwide. However, the actual prevalence of skin cancer in these countries should be investigated. Further research on the prevalence of skin cancer across different continents is required to develop more effective cancer management strategies and control the spread of the disease. [Display omitted] •Skin cancers are highly prevalent in white-skinned populations with sunburns; basal cell carcinoma is the most prevalent.•Australia and New Zealand have the highest incidence rates of skin cancers.•The highest incidence and mortality rates of melanoma skin cancer were recorded in Europe.•The highest incidence and mortality rates of non-melanoma skin cancers were recorded in North America and Asia.•The incidence of non-melanoma skin cancer is 18–20 higher than melanoma skin cancer, resulting in more deaths.